Structure and operational properties of porous cermets on the basis of alloyed steel scale; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 2 - Tubalov N. P. (Mathematics and mechanics.Physics, 2007)
Заглавие с титульного листа